Using Kappa Cohen for Expected Agreement of Math X-Quest Learning Media for in Support of SDGs-4 (Quality Education) Context - Arianti, Putri Dwi; Mukti, Taufiq Satria; Nur’aini, Luthfiah Hamidah (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Media quality needs to be proven in certain ways, one way is by expert assessment. In this paper, we examine the quality of Math X-Quest media which is assessed by two experts using the Cohen Kappa method. This activity aims to obtain validity in the form of feasibility of the contextual game-based Math X-Quest media that helps students understand the concept of three-variable linear equations through balancing activities, connecting abstract mathematical ideas with concrete experiences. The rater assessment consisted of aspects of the material and learning media. Analysis of the rater results was carried out using descriptive statistics with the Crosstabs technique. The results obtained showed that 2 raters had the same view on the quality of the assessment with a value of 0.69 spearman correlation. Meanwhile, the quality of X-Quest obtained a suitability score of 0.872 from the two expert assessors, indicating a near-perfect Cohen Kappa Agreement index. Thus, it can be concluded that X-Quest is suitable for use in mathematics learning which can support improving the quality of education as envisioned in SDG 4.